Analisis Akuntansi untuk Mata Uang Kripto: Tantangan Dan Solusi Dalam Standar Pelaporan Keuangan - Judijanto, Loso; Kusnadi, Iwan; Al-Amin, Al-Amin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research examines challenges and solutions in financial reporting standards for cryptocurrencies, a rapidly evolving field with unique characteristics and complexities. It highlights key obstacles such as price volatility, unclear accounting treatment, and difficulties in digital asset valuation. On the other hand, it also explores potential solutions, including the adoption of blockchain technology to improve transparency and traceability of transactions, the use of advanced algorithms for verification and valuation, and international cooperation in the development of adaptive guidelines. By integrating these approaches, accounting for cryptocurrencies can be improved to be more reliable and compliant with global financial reporting standards. The results of this study provide a scientific foundation for further developments in cryptocurrency accounting practices, which are necessary to win stakeholder trust and support wider adoption in the digital economy